Responses of carbon exchange characteristics to meteorological factors, phenology, and extreme events in a rubber plantation of Danzhou, Hainan: evidence based on multi-year data - Yang, Siqi; Wu, Zhixiang; Yang, Chuan; Song, Bo; Liu, Junyi; Chen, Bangqian; Lan, Guoyu; Sun, Rui; Zhang, Jie (Frontiers in Ecology and Evolution, 2023)
On Hainan Island, a rubber plantation that occupies a large swath of land, plays an important role in the regional carbon budget. However, the carbon exchange of the rubber plantation is poorly understood. In this study, using the eddy covariance methods we measured carbon metrics in the rubber plantation for 13 years from 2010 to 2022. We clarified that the rubber plantation is a carbon sink and the annual net ecosystem exchange (NEE), ecosystem respiration, and gross primary production were -911.89±135.37, 1528.04±253.50 and 2439.93±259.63 gC·m-2·a-1, respectively. Carbon fluxes differed between inter-annual years; specifically rainy season fluxes were nearly double dry season fluxes. Radiation explained 46% of the variation for NEE in rainy season and temperature explained 36% of variation for NEE in dry season. LAI explained the highest proportion of the monthly variation in NEE (R2=0.72, P<0.001), indicating that when hydrothermal conditions are sufficient phenology may the primary factor controlling carbon sequestration of rubber plantation. Due to climate change, there is an increasing probability of extreme climate events such as typhoons, heat waves, and drought. Thus, we compared NEE before and after such events and results show extreme climate events reduce carbon uptake in the rubber plantation. We found that typhoons reduced NEE to varying degrees on different timescales. Heat waves generally decreased NEE during the day but recovered quickly and increased carbon uptake if there was sufficient rainfall. Drought reduced carbon uptake and continued to decrease even after rainfall. Estimating the carbon sink capacity of the rubber plantation and studying the response to regional environmental changes are important for both applied research (carbon sink research and market trading, sink enhancement and emission reduction, etc.) and basic research (land use change, phenology change, etc.).